The Relative Roles of Peer and Parent Predictors in Minor Adolescent Delinquency: Exploring Gender and Adolescent Phase Differences - Defoe, Ivy N.; Dubas, Judith Semon; van Aken, Marcel A. G. (Frontiers in Public Health, 2018)
Social learning theories assume that delinquent peer norms and/or peer pressure are the components of delinquent peer socialization that lead to subsequent adolescent delinquency. However, these specific peer influences are rarely investigated. Moreover, social learning theories such as coercion theory posit that parenting behaviors also play an important role in the development or prevention of delinquency. However, surprisingly, little research has investigated whether parent behaviors could moderate the link between the above-described peer influences and adolescent delinquency. Hence, using structural equation modeling, the current 1-year longitudinal study investigated these questions among ethnically-diverse Dutch adolescents (N = 602; Mage = 13.50; 46.42% female at baseline), who were mostly between12 and 15 years old. Additionally, using multi-group models, and a stringent p-value of p < 0.01, we explored whether gender and adolescent phase (i.e., early versus middle adolescence) further moderated these links. The majority of the analyses, resulted in non-significant findings. Specifically, in our non-multi group model, we found no significant peer, and family effects for the entire sample. However, for our multi-group models, we found that higher levels of negative mother-adolescent relationship quality exacerbated the link between peer pressure and subsequent early adolescent boys' delinquency 1 year later, while low levels of mother-adolescent negative relationship quality reversed the association. That is, low levels of mother-adolescent negative relationship quality attenuated the link from higher levels of peer pressure to higher levels of delinquency, but only in early adolescent boys. These findings existed above and beyond significant links from prior adolescent delinquency (T1) to future adolescent delinquency (T2). To conclude, although this was not the case for most adolescents, for early adolescent boys fewer negative interactions between mother and adolescents at an earlier time point (in advance) could potentially curtail the negative effects that delinquent peer pressure has on delinquency in the future. Implications for theory and practice are discussed.